CO2 activation on small Cu-Ni and Cu-Pd bimetallic clusters (2019)
The use of CO2 to produce methanol is a reaction of growing interest, where bimetallic Cu-M catalysts become relevant as an alternative to the known Cu/Zn/Al2O3 catalyst. However, there is a lack in the understanding of bimetallic systems at atomic label and its capability towards CO2 activation, a key step in CO2 valorization. In this work, Cu-Pd and Cu-Ni small clusters are studied using DFT. Among the evaluated bimetallic systems, the binding of CO2 on Cu3Pd has the highest thermodynamics stability (28.82 kcal/mol) and the lowest energy barrier (40.91 kcal/mol). The activation energy for the dissociation of CO2 (CO2